Vitamin D level in patients with pterygium - Kara,Necip (2017)
ABSTRACT Purpose: To evaluate blood vitamin D level in patients with pterygium. Methods: This prospective study, compared 58 eyes of 58 healthy individuals (control group) with 63 eyes of 63 patients with pterygium (study group). Subjects were stratified by time spent indoors or outdoors. Participants were given comprehensive ophthalmic examinations; blood 25-hydroxyvitamin D (nmol/L) was assayed. Results: Vitamin D level was significantly higher in men with pterygium than without it (p=0.020), but the difference was not significant in women (p=0.86). In the pterygium group, vitamin D level was significantly increased in participants with outdoor activity (p=0.010). In the control group, vitamin D levels did not differ significantly with indoor and outdoor activity (p=0.126). Conclusion: Vitamin D level in participants with pterygium was significantly increased only in men and in those with more outdoor activity.